2021
DOI: 10.1111/jocs.16089
|View full text |Cite
|
Sign up to set email alerts
|

Slow gait speed is associated with worse postoperative outcomes in cardiac surgery: A systematic review and meta‐analysis

Abstract: Background Frailty is associated with poorer outcomes in cardiac surgery, but the heterogeneity in frailty assessment tools makes it difficult to ascertain its true impact in cardiac surgery. Slow gait speed is a simple, validated, and reliable marker of frailty. We performed a systematic review and meta‐analysis to examine the effect of slow gait speed on postoperative cardiac surgical patients. Methods PubMED, MEDLINE, and EMBASE databases were searched from January 2000 to August 2021 for studies comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Other studies29-31 have suggested that slower gait speed cutoff scores (<0.8 m/s) put patients at higher risk for frailty, hospitalization, mortality, and poor outcomes. While this study had a slower Gait Speed cutoff (≥0.57 m/s), this could be due to a more acute critical condition, use of a self-selected gait speed, and/or the logistics of managing lines and tubes, as well as the number of support personnel required to ensure safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies29-31 have suggested that slower gait speed cutoff scores (<0.8 m/s) put patients at higher risk for frailty, hospitalization, mortality, and poor outcomes. While this study had a slower Gait Speed cutoff (≥0.57 m/s), this could be due to a more acute critical condition, use of a self-selected gait speed, and/or the logistics of managing lines and tubes, as well as the number of support personnel required to ensure safety.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence about the use of a cutoff score when transitioning ambulation from physical therapy to nursing service. Cutoff scores from certain outcome measures have been used to suggest patient discharge location [26][27][28] and risk of frailty, rehospitalization, mortality, and morbidity, [29][30][31] but never to support the transition of mobility responsibility while patients are still admitted in an acute care setting. The primary aim of this study is to explore the feasibility of using cutoff scores for AM-PAC, Perme, and gait speed to determine when it is most appropriate to transition ambulation from physical therapy service to nursing service.…”
mentioning
confidence: 99%
“…22 Despite the inconsistency of the definition of frailty, it can be assessed using a variety of tools such as the clinical frailty scale or more objective Fried frailty criteria including gait speed and handgrip strength, which are useful predictors of all-cause mortality and cardiovascular disease and death in elderly surgical and non-surgical patients. [23][24][25] Similarly, standardised screening and assessments exist for the diagnosis of malnutrition and sarcopenia, which demonstrated significant overlap with frailty. [26][27][28] In summary, the elderly, frail, malnourished and sarcopenic patient is especially at risk for perioperative complications, however, many options for medical, physiological and psychological optimisation exist.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…All these factors contribute to a reduction in functional capacity 22. Despite the inconsistency of the definition of frailty, it can be assessed using a variety of tools such as the clinical frailty scale or more objective Fried frailty criteria including gait speed and handgrip strength, which are useful predictors of all-cause mortality and cardiovascular disease and death in elderly surgical and non-surgical patients 23–25. Similarly, standardised screening and assessments exist for the diagnosis of malnutrition and sarcopenia, which demonstrated significant overlap with frailty 26–28.…”
Section: Introductionmentioning
confidence: 99%
“…Ersten Studien zufolge ist die Testung von Frailty auf Grundlage der Gehgeschwindigkeit ein geeignetes Scree-ning-Tool [28]. Die Diagnostik von präoperativer Frailty mit einer Gehgeschwindigkeit von < 0,83 m/s konnte bei herzchirurgischen Eingriffen eine Verdopplung der Krankenhausmortalität und ein signifikant erhöhtes Risiko für Infektionen, akutes Nierenversagen, Intensivstationsaufenthalten sowie weitere Adverse Events nachweisen [30]. In einer anderen Studie wurden für die Gehgeschwindigkeit eine Sensitivität von 99 % und Spezifität von 64 % für das Vorliegen einer Frailty angegeben [28].…”
Section: Assessmentbasierte Einschätzungunclassified